2022
DOI: 10.1007/s10637-021-01203-5
|View full text |Cite
|
Sign up to set email alerts
|

Classification and regression tree for estimating predictive markers to detect T790M mutations after acquired resistance to first line EGFR-TKI: HOPE-002

Abstract: Background and objective: Osimertinib as rst-line treatment for patients with non-small cell lung cancer (NSCLC) harboring epidermal growth factor (EGFR) mutations remains controversial. Sequential EGFRtyrosine kinase inhibitor (TKI) might be superior to the rst line osimertinib in patients at risk of developing acquired T790M mutations.Methods: We enrolled consecutive patients with EGFR-mutated (deletion 19 or L858R) advanced NSCLC treated with rst-line drugs and evaluated predictive markers using classi cati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This is important for improving the quality of life for LCBM patients. Nevertheless, targeted therapies and immunotherapies for LCBM still face challenges, such as still being in the animal testing stage or drug resistance, and there is still a long way to go before they can be used as effective LCBM treatments[ 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important for improving the quality of life for LCBM patients. Nevertheless, targeted therapies and immunotherapies for LCBM still face challenges, such as still being in the animal testing stage or drug resistance, and there is still a long way to go before they can be used as effective LCBM treatments[ 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33] In this study, sex and pathological type were not associated with clinical outcomes, whereas several previous studies have shown that sex and pathological type were associated with the clinical outcome. [34][35][36][37] The reason may be because our study was retrospective, follow-up did not strictly adhere to the prospective study protocol, and some patients were not had advanced disease at the time of diagnosis. The majority of patients had adenocarcinoma, and adenocarcinoma and Asians are the dominant groups treated with targeted therapy, whereas the patient mix and carcinoma type differ between Asian and non-Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-TKIs are the preferred choice for EGFR-mutant NSCLC [30,31], but whether these patients could beneft from ICIs treatment remains unknown. Recently, clinicians and researchers focused on the precision and individualized ICIs treatment for these patients [32][33][34].…”
Section: Discussionmentioning
confidence: 99%